PROTEIN, AMINO ACIDS AND NUCLEIC ACIDS METABOLISM DISORDERS - P. F. Litvitskii; L. D. Mal'tseva (Вопросы современной педиатрии)
This lecture reviews types, causes and key points of pathogenesis of protein, amino acids and nucleic acids metabolism disorders, as well as their clinical implications.